The Role of the Code Blue Team Nurses in Managing Cardiac Arrest Patients in Hospitals: A Systematic Review - Wawan Joko Apriyanto; Indah Winarni; Setyoadi (International Journal of Science and Society, 2020)
The purpose of this study is to find out how the role of the code blue team nurses in handling patients with cardiac arrest in the hospital. A systematic review has been carried out through several stages, namely making questions, identifying, eligibility, selecting article inclusions, screening, and appraisal. The selection process is listed in the review systematic framework and 6 article articles are obtained. The articles are summarized and assessed by JBI (Joanna Briggs Institute). A systematic review show different results, as follows: majority of nurses felt confident and competent during the call, and that nontechnical skills were performed more frequently than technical skills. These outcomes support the continued use of ongoing simulation training to further improve team performance, maintain member confidence, and assure quality patient care. Role nurse is increase teamwork and interprofessional team training, increased knowledge and skills, communication, increased confidence and comfort, simulation experience, debriefing and reflective learning. There is no significant difference in survival from cardiac arrest when a standardized ‘‘Code Blue Team’’ is utilized, regardless of the time of day or week. Comparison of MET (Medical Emergency Team) and code blue calls before and after implementation of the ADDS (Acute Deterioration Detection System): there was a significant increase in activations proportional to admissions found in the year after the implementation. The role of a code blue team nurse includes non-medical: communication skills, leadership skills, team interaction skills, and task coordination skills. Medical skills: chest compression skills and early defibrillation skills.